Estrutura genética das populações de abelhas africanizadas (Apis mellifera L.) do Brasil determinada por meio de polimorfismos do DNA mitocondrial - Collet, Thaís (Universidade Federal de São Carlos, 2004)
The Apis mellifera subspecies are classified into evolutionary branches originally distributed in the African (branches A and Y), European (branches C and M) and Asian (branch O) continents. This distribution has been changing due to the subspecies introductions to other countries, mainly occurred by beekeeping activities. Therefore, population genetics studies on the already established and newly introduced populations have increased. The introduction of the African honeybee in American continent, known as Africanization, became one of the most studied events related to Apis mellifera introductions. The characterization of different lineages that contribute to hybrid populations is the first approach of the studies related to subspecies introductions. In this way, we describe the restriction patterns obtained from a 16S region fragment of the mitochondrial DNA. These patterns enables the differentiation among races from the three evolutionary branches using only one region of the mitochondrial genome, without the requirement of amplification of other regions. The determination of the racial composition of the hybrid product of Africanization in America led to the development of diverse tools suitable for it, including mtDNA analysis. We present here the results obtained with the polymorphism produced by Dra I endonuclease in a fragment of the tRNAleu_COII intergenic region. These results contribute to the understanding of the genetic structure of Africanized populations from Brazil. From 11 mitotypes observed, three have not been described in previous analysis and present similar patterns to some found at Iberian Peninsula. The most frequent patterns were the African A1 and A4, probably introduced in Brazil by Apis mellifera scutellata in 1956. Although the patterns analyzed in this work are more informative than the ones used until now in Africanized populations, the distribution of A1 pattern evidences the importance of using other mitochondrial regions to identify its origin. Working with these regions and other markers, it will be possible to clarify the genetic structure of Africanized honeybees of the Americas.
Keywords: Genética de populações; Abelha - africanizadas; Apis mellifera; DNA mitocondrial; CIENCIAS BIOLOGICAS::GENETICA